Transaction costs and the sharing economy - Anders Henten; Iwona Windekilde (International Telecommunications Society (ITS), 2015)
The paper discusses the so-called sharing economy from an industrial structure perspective. The illustrative cases examined are Airbnb and Uber. The research question raised is concerned with the extent to which transaction cost theory can be used to explain the changing industrial structures in the application areas that the Internet-based platforms are addressing and how other theoretical frameworks can be helpful in understanding these developments. The paper concludes by proposing a theoretical framework for analyzing the structural implications of the sharing economy based on theories on multi-sided platforms, transaction costs, and substitution and complementation.
Keywords: 330